GRASS AS REINFORCEMENT OF POLYPROPYLENE - Caraschi, J.C.; Prates, G. A.; Leão, A. L.; Almeida, C. C. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Considerable interest has been generated in the use of lignocellulosic fibers as filler and reinforcements in polymeric composite. In this work polymeric composites were obtained from elephant grass fiber and polypropylene (PP/Grass). The effects of the content filler and accelerated aging on the mechanical properties of polypropylene composites reinforced with elephant grass fiber were evaluated. The composites were prepared through the extrusion process of polypropylene with grass fiber in ratio 15 and 25% wt. The specimens were injection molded according to American Society for Testing and Materials standards. In the evaluation of the composite properties, the obtained results noticed that increasing the filler amount resulted in a decrease of mechanical properties and increase in flow index, shore D hardness and density. The composites did not show significant differences as function of accelerated aging. The results showed that composite properties are extremely favorable when compared to other commercial systems reinforced by inorganic fillers.